Concurrent Infective Endocarditis and Empyema From Salmonella arizonae - Derin Allard; Helen Banh; Gracie Swanberg; Lisa Ryan (Annals of Internal Medicine: Clinical Cases)
Although often associated with gastroenteritis, up to 30% of Salmonella infections are extraintestinal. Fewer than 50 cases of Salmonella empyema have been reported in the past century, and less than 2.9% of bacterial endocarditis cases are attributed to Salmonella species. Salmonella enterica subspecies arizonae generally causes mild disease and has been associated with reptiles or products containing rattlesnakes. We report the patient case of a 38-year-old man who presented to the hospital in septic shock and was found to have concurrent Salmonella bacteremia, endocarditis, and empyema with subspecies arizonae.